STUDENTS’ DIGITAL NARRATIVE WRITING PROJECT - Mardiana, Wiwik; Feriyanto; Afkar, Taswirul; Krisdiana, Amy (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2024)
In the 21st century, technological progress has revolutionized education, emphasizing the 5Cs (communication, communities, connections, comparisons, and culture) in English language teaching. This evolution presents challenges for educators to innovate learning methods, including Project-Based Learning that integrates technology and cultural elements. This study explores students' perspectives on a writing project that combines extensive reading and narrative writing using Book Creator, focusing on the impacts and cultural aspects. Using a qualitative case study design, data was gathered through interviews and analyzed with thematic analysis. The participants were fifteen second-semester students. The findings show that, according to the students, a culture-based writing project with technology integration requires structured processes to help develop ideas. This approach not only improves writing skills but also enhances cultural understanding. The study suggests that the learning model, along with its positive outcomes and contributing factors, could provide a valuable framework for university-level writing courses. Keywords: project-based learning, writing, narrative